Human smugglers or smuggled persons? An approach to the situation of youth accused of human smuggling in southern Spain - Carvalho da Silva, Jacqueline (My University, 2023)
Spain's southern border is a gateway for irregular immigration through unauthorized routes. The maritime routes from Africa to the Canary Islands and Andalusia represent a door to Europe through which different profiles of people try to cross using small boats. The mafias that charge for facilitating these dangerous transfers profit from the lack of secure routes for safe immigration. In a recent report, the United Nations Office on Drugs and Crime (UNODC) notes that a large number of people are being arrested just after arriving thought the Canary Island route, accused of smuggling migrants. The report questions whether the weight of the law is falling on people who have little to do with the criminal networks that move the boats. During fieldwork in a prison in Andalusia in the framework of the JEPRAN project (Former Foster Youths in Andalusian Prisons, 2021-2023) and seeking to identify different profiles of young people in prison, a surprising number of young people accused of human smuggling were identified. In a second structured interview with them, we inquired about the circumstances of their detention. This communication will focus on presenting the results found, seeking to approach from their testimonies, this worrying situation.
Keywords: Crimen - Congresos; Youth, Prison, Human smuggling